PENGEMBANGAN BUKU PANTAU KESEHATAN GIGI ANAK USIA DINI - Febrianti, Sri; Halid, Idham; Muliadi, Muliadi (NHM PRESS, 2023)
Az-Zahra Islamic Kindergarten is a kindergarten located on Jl. R. Sahbudin Forestry Complex Block E 13 Mayang Mangurai, Alam Barajo District, Jambi City. The kindergarten has never had a dental health check-up and about 5 students have experienced toothache during the teaching and learning process and 2 students have been absent from school due to toothache. Furthermore, based on the results of a survey with interviews with 10 parents via Smart Phones, they said that their children rarely brush their teeth before going to bed at night, usually only brush their teeth when bathing in the morning and evening and rarely even check their children's teeth at the dental and oral health service. Research and Development/ (R&D). This study aims to develop dental and oral health education media for parents in maintaining dental health through an early childhood dental health monitoring book. The results of the assessment from the book and material expert validators are known to have a feasibility score of 82% and 83% with a very decent category (without revision). so that the dental health monitoring book deserves to be tested by users. user feasibility test to 30 parents, especially mothers in Az-Zahra Islamic Kindergarten and get very decent results without revision. The dental health monitoring book is suitable as a medium for dental health education for parents